Tolerance to FVIII: Role of the Immune Metabolic Enzymes Indoleamine 2,3 Dyoxigenase-1 and Heme Oxygenase-1 - Matino, Davide; Afraz, Sajjad; Zhao, George; Tieu, Paul; Gargaro, Marco; Fallarino, Francesca; Iorio, Alfonso (Frontiers in Immunology, 2020)
The occurrence of neutralizing anti-FVIII antibodies is a major complication in the treatment of patients affected by hemophilia A. The immune response to FVIII is a complex, multi-factorial process that has been extensively studied for the past two decades. The reasons why only a proportion of hemophilic patients treated with FVIII concentrates develop a clinically significant immune response is incompletely understood. The “danger theory” has been proposed as a possible explanation to interpret the findings of some observational clinical studies highlighting the possible detrimental impact of inflammatory stimuli at the time of replacement therapy on inhibitor development. Recent studies have provided evidence that multiple interactions involving central and peripheral mechanisms of tolerance are integrated by the host immune system with the environmental conditions at the time of FVIII exposure and influence the balance between immunity and tolerance to FVIII. Two key immunoregulatory enzymes (IDO, HO-1) have been studied in hemophilia patients and pre-clinical models showing that the ability of the host immune system to induce such regulatory proteins under inflammatory conditions can influence the balance between immunity and tolerance to the exogenous FVIII. We propose that the host immune system is often challenged to assess FVIII under inflammatory conditions (e.g. bleeding, infections) but the upregulation of mechanisms of adaptive immune tolerance can be at work to control inflammation and promote long-term unresponsiveness to the therapeutically administered factor.